From Purchasing to Supply Management - Stolle, Michael A. (Springer, 2017)
For more than 20 years, researchers and practitioners claimed a transition from traditional purchasing to strategic supply management. However, very few companies actually have been able to make this transition happen. Given the fact that most of the actual practices applied by world-class companies are well known, the question remains why so many companies failed along the way. What does it take to overcome the barriers of purchasing evolution - and what are the benefits?